Impact of pre-sarcopenia and sarcopenia on biological and functional outcomes in individuals with chronic obstructive pulmonary disease: a cross-sectional study. - Sepúlveda Loyola, Walter; Pereira Junior, Paulo Sérgio; Valenzuela- Fuenzalida, Juan José; Santillán-Zuta, Milton; Suziane Probst, Vanessa (Nutrición Clínica y Dietética Hospitalaria, 2024)
Introduction: The impact of pre-sarcopenia, sarcopenia on important clinical and biological outcomes in individuals with Chronic obstructive pulmonary disease (COPD) have not been fully investigated. Objective: To analyze the impact of pre-sarcopenia and sarcopenia on balance, muscle mass, peripheral and respiratory muscle strength and inflammatory and oxidative stress biomarkers in individuals with COPD. Methods: sixty-one patients diagnosed with COPD were included, stratified into three groups: without sarcopenia (n = 33; 69 ± 6 years), with pre-sarcopenia (n = 15; 66 ± 6 years) and with sarcopenia (n = 13; 71 ± 7 years), according to the European Working Group on Sarcopenia in Older People. It was assessed respiratory muscle strength, through maximum inspiratory pressure (MIP) and maximum expiratory pressure (MEP), handgrip strength (HGS) and body composition analysis with bioimpedance. Inflammatory and oxidative stress biomarkers were analysed from peripheral blood. Results: The prevalence of pre-sarcopenia and sarcopenia in individuals with COPD was 36% and 25%, respectively. Individuals with sarcopenia exhibit inferior muscle mass, peripheral muscle strength, respiratory muscle strength, and balance compared to their counterparts (p<0.05 for all). In addition, individuals with sarcopenia presented lower levels of protein oxidation (p=0.015) and higher levels of interleukin-1ɓ (p=0.035) compared to those without sarcopenia. Individuals with pre-sarcopenia presented lower levels of antioxidant activity (p=0.045) and higher levels of C-reactive protein (p=0.035). Conclusion: Individuals with COPD who have sarcopenia exhibit diminished muscle mass, impaired balance, and reduced peripheral and respiratory muscle strength in comparison to those with pre-sarcopenia or without sarcopenia. In addition, the presence of sarcopenia and pre-sarcopenia is probably linked by biological mechanisms related to systemic inflammation and oxidative stress.